Dynamics of the serum bilirubin level during bile ducts drainage in patients with hilar tumor stenosis and jaundice - Palytsya, R.; Markulan, L.; Tsema, Ie.; Dubenko, D.; Batiuk, A.; Susak, Ya. (Journal of Education, Health and Sport, 2021)
Palliative bile duct decompression with various modifications are currently performed in 75-80% of patients with hilar stenosis caused by the tumor. The main goal of palliative care is to reduce the manifestations of jaundice, intoxication, pain syndrome, prolong life period and improve patient’s conditions for chemotherapy. Objective: to evaluate the effectiveness of bile ducts antegrade drainage methods by bilirubin reducing in the palliative treatment of patients with jaundice due to hilar stenosis caused by the tumor. Materials and methods. In a prospective study included 78 patients with hilar obstructive jaundice, who were underwent of palliative antegrade draining of bile ducts: percutaneous transhepatic cholangiostomy (group PTC) - n = 24, externally-internal suprapapillary cholangiostomy (group EISC) - n = 26, percutaneous transhepatic antegrade endobiliary stenting (group PTAES) - n = 28. Endpoints of the study: total serum bilirubin before the procedure, after 3, 7 days and every 10 days for two months. The mean values of bilirubin and the average percentage of decrease in its value at each of the control periods were evaluated in relation to the initial level. Also, at the same time, the cumulative percentage of patients in which bilirubin had a value of ≤34.2 μmol / L (2 mg / dL) or ≤ 85.5 μmol / L (5 mg / dL) was assessed - the threshold values at which a certain type of chemotherapy is possible. Results. In all groups, there was a decrease in the average values of bilirubin levels with an increase in the time passed after the procedure. At all control periods, the mean bilirubin values and the percentage of decrease in the mean bilirubin values did not differ statistically between groups (all p < 0.05). The highest rates of decrease in the level of bilirubin were observed during the first 10 days (about 60.0%). From the 10th to the 60th day, the decrease in the level of bilirubin was approximately 20% from the initial one. The cumulative percentage of patients with the bilirubin level on the 60th day ≤ 34.1 μmol / l (2 mg / dl) was 45.8% in the EISC group, 64.5% in the PTC group, and 63.9% in the PTAES group (p = 0.257) in a month these indicators were 11.7%, respectively; 12.5% and 17.9% (all p <0.05). The decrease in the level of bilirubin ≤ 85.5 μmol / L (5 mg / dL) was more rapid. So, already after 10 days, the cumulative percentage of such patients in the groups exceeded 50.0%: 58.3% in the EISC group, 63.6% in the PTC group, 57.7 % in the PTAES group (p = 0.26) in a month these indicators were respectively 83.3%; 77.3% and 80.8%, after two months, respectively 91.7%, 86.4 and 100% (p = 0.80). Conclusions. The methods of transcutaneous bile ducts drainage/stenting effectively reduce the level of total bilirubin in patients with obstructive jaundice due to hilar stenosis caused by tumor and have no statistically significant differences in the dynamics of bilirubin level within two months of observation.